HUBUNGAN PENDIDIKAN TERHADAP PEMBERIAN ASI EKSLUSIF PADA BAYI 6-12 BULAN - Wijayanti, Adhika; Adhika Wijayanti; Yuli Suryanti; Sartika Dwi YP; Fitria Aptika (IKES Payung Negeri Pekanbaru, 2025)
Aging is a condition in which a person experiences gradual physical, mental, and social decline, resulting in an inability to perform daily activities. As humans age, a degenerative aging process occurs, which typically impacts the person's psyche and self, not only physical but also cognitive. Diabetes mellitus is a metabolic disorder characterized by the loss of glucose homeostasis, accompanied by impaired carbohydrate and fat metabolism. The butterfly pea plant has been extensively studied and proven to have various benefits. Butterfly pea leaves have anti-inflammatory properties. The purpose of this study was to determine the effectiveness of administering butterfly pea tea on reducing blood sugar levels in the elderly in Taraman Jaya village. This study was a pre-experimental, pre-test, post-test study without a control group. The population in this study was 46 people aged 60-74 years in Taraman Jaya village from April to May 2024. The obtained p-value was 0.000 <α = 0.005, meaning p <α. There is effectiveness of administering butterfly pea tea on reducing blood sugar levels in the elderly in Taraman Jaya village.